Experimental determination of the suture behavior of aortic tissue in comparison to 3D printed silicone modelling material. (December 2020) - Riedle, Hannah; Chaban, Ryan; Ghazy, Ahmed; Piplat, Charlotte; Dorweiler, Bernhard; Franke, Jörg
Abstract: The imitation of biological tissue in a synthetic physical model can benefit many medical applications, e.g. pre surgical planning or education. For a quantitative validation of the model's mechanical behavior, standardized testing on both, the biological original and the artificial material, is necessary. In four parts, this study focuses on the biomechanical analysis of the impact of sutures for aortic modelling using 3D printed silicone. Testing methods are developed and executed on biological and synthetic samples. The first part is the determination of the pullout strength of a single stitch. The second part is the investigation of the reduction of the tensile strength and elongation of tensile bars due to stitching. Third, the tensile testing of biological and artificial vessels repaired with an anastomosis gives information about the transferability to real surgical applications. A qualitative feedback study with surgical experts concludes the evaluation. The study reveals that the pullout strength is independent from the fiber or notch direction, but that repaired aortic tensile bars show a dependency on the fiber direction of the tissue. Additionally, the circular seam of the anastomosis provides a more stable connection than multiple single stitches. For the artificial models, the mechanical behavior mainly depends on the mechanical properties of the base silicone, here represented by the Shore A hardness, rather than the manufacturing process. When compared to the biological original the most similar material varies depending on the mechanical property in focus. Graphical abstract: Image 1 Highlights: Comparison of aortic tissue and 3D printed silicone samples. Determination of the pullout strength of a single stitch. Standardized mechanical testing of sutured tensile bars. Tensile testing of biological and artificial vessels repaired with an anastomosis. Qualitative, subjective evaluation of the silicone samples in comparison to the biological original.